Narrative Persuasion - Kai Barron; Tilman Fries (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
Modern life offers nearly unbridled access to information; it is the harnessing of this information to guide decision-making that presents a challenge. We study how one individual may try to shape the way another person interprets objective information by proposing a causal explanation (or narrative) that makes sense of this objective information. Using an experiment, we examine the use of narratives as a persuasive tool in the context of financial advice where advisors may hold incentives that differ from those of the individuals they are advising. Our results reveal several insights about the underlying mechanisms that govern narrative persuasion. First, we show that advisors construct self-interested narratives and make them persuasive by tailoring them to fit the objective information. Second, we demonstrate that advisors are able to shift investors' beliefs about the future performance of a company. Third, we identify the types of narratives that investors find convincing, namely those that fit the objective information well. Finally, we evaluate the efficacy of several potential policy interventions aimed at protecting investors. We find that narrative persuasion is difficult to protect against.
Keywords: D83; G40; G50; C90; 330; narratives; beliefs; financial advice; conflicts of interest; behavioral finance